The development of framework for a lightweight metallic drone frame using selective laser melting (SLM) 3D printing machine - Abu Zaki, Muhammad Syafiq Syazwan (2025)
The efficient execution of heavy-duty tasks by drones necessitates a robust frame capable of lifting heavy objects from a stable, elevated position. However, traditional solid materials contribute to excessive weight, accelerating battery deterioration. Moreover, complex designs pose challenges for conventional machining methods. This study aims to design a lightweight and sturdy drone frame using stainless steel via generative design. Strength and stability are evaluated through simulation and experimentation. The proposed solution leverages additive manufacturing, specifically Selective Laser Melting (SLM) 3D printing, with stainless steel powder. To design a drone frame that is suitable for that requirement, first needs to study the machine's behaviour and the mechanical properties of the material. To understand the machine's capability, the experiment that was decided is a surface roughness test by experimenting with the printing orientation of specimens. The specimens were printed using three parameters: the effect of surface area, the effect of height, and the effect of printing angle. Then, the specimens underwent a surface roughness test to determine which printing orientation was the best for manufacturing the drone frame. For the mechanical properties, the experiments that were executed were impact tests and tensile tests. The specimens were drawn first using Autodesk Fusion 360, guided by the American Society for Testing and Materials (ASTM), and fabricated using a Selective Laser Melting (SLM) 3D printing machine. The parameters for these experiments are the material state of the stainless steel powder (virgin and recycled powder), the thickness of the specimens, and the coordination of the specimens on the production bed. After finishing all the physical experiments, the process proceeds to the simulation experiment. First, sketch multiple designs of the drone frame. Those designs that were sketched will be drawn using Autodesk Fusion 360 and undergo a Generative Design process. After that process, the design file was exported to STEP format (.step) for simulation using the Static Structural study in Finite Element Analysis (FEA) within Autodesk Fusion 360. This allowed for the evaluation and selection of the best drone frame design before proceeding to the manufacturing stage. The best design that was selected from the FEA simulation test is manufactured using the Additive Manufacturing method, which is the Selective Laser Melting (SLM) 3D Printing machine using stainless steel powder as the main material. As a result, a sturdy and lightweight drone frame was successfully fabricated by combining innovative design strategies with advanced manufacturing techniques. The feasibility of generating sufficient thrust from the selected brushless motors to lift the frame was also evaluated. This research offers a practical solution to the challenges of weight, strength, and complexity in drone frame construction.